PRACTICAL IMPLEMENTATION OF NEUROMARKETING IN DIFFERENT BUSINESS INDUSTRIES: CHALLENGES AND TRENDS - Sevic, Nevenka Popovic (Annals of Spiru Haret University. Economic Series, 2022)
Abstract Over the last decade, new technological progress has enabled the researchers to use neuroscience not only for scientific but also for marketing studies, so they can explore, at the same time, conscious and unconscious drivers of consumer behaviour in real daily situations. Applying brain science to consumer behaviour, neuromarketing—a new innovative marketing research discipline—examines consumers’ response (sensory, motor, and cognitive) to advertising stimuli. This article focuses on three key areas: literature review, challenges and limitations of neuromarketing, and neuromarketing trends, with several concrete real-life examples in different business industries. Practical challenges and limitations within the neuromarketing research, such as ethics, accessibility, costs and timing, but also side effects, are discussed. At the end, this article emphasizes many practical implementations of neuromarketing in different business branches, with the adoption of academic and scientific neuroscience researches to commercial purposes.